A narrative approach to studying symbolic boundaries among drug users: A qualitative meta-synthesis. (August 2016) - Copes, Heith
The narrative study of identity promotes the idea that people develop social identities by telling stories about themselves and others. Through these stories, people associate with desired groups and create social boundaries separating them from the less desirable. While all people engage in boundary work, it is especially important for those who are physically or socially near members of stigmatized groups (e.g. drug users). My aim here is to examine how drug users narratively create symbolic boundaries to differentiate types of users (i.e. functional vs. dysfunctional). To elaborate on the general characteristics of these symbolic boundaries, I rely on qualitative meta-synthesis of research on boundary work among drug users and insights from my own research with people who use drugs. I draw from narrative identity theory to locate the places from which they derive their stories when creating symbolic boundaries and the content of the symbolic boundaries. I discuss the role of symbolic boundaries in facilitating drug use and inhibiting recovery and conclude by discussing the theoretical importance of using narrative criminology for understanding boundary development, boundary maintenance, and the content of boundaries.